Dietary Sodium Restriction Reverses Vascular Endothelial Dysfunction in Middle-Aged/Older Adults With Moderately Elevated Systolic Blood Pressure - Jablonski, Kristen L.; Racine, Matthew L.; Geolfos, Candace J.; Gates, Phillip E.; Chonchol, Michel; McQueen, Matthew B.; Seals, Douglas R. (Journal of the American College of Cardiology, 2013)
This study sought to determine the efficacy of dietary sodium restriction (DSR) for improving vascular endothelial dysfunction in middle-aged/older adults with moderately elevated systolic blood pressure (SBP) (130–159 mm Hg) and the associated physiological mechanisms. Vascular endothelial dysfunction develops with advancing age and elevated SBP, contributing to increased cardiovascular risk. DSR lowers BP, but its effect on vascular endothelial function and mechanisms involved are unknown. Seventeen subjects (11 men and 6 women; mean age, 62 ± 7 years) completed a, randomized crossover study of 4 weeks of both low (DSR) and normal sodium intake. Vascular endothelial function (endothelium-dependent dilation; EDD), nitric oxide (NO)/tetrahydrobiopterin (BH4) bioavailability, and oxidative stress-associated mechanisms were assessed following each condition. Urinary sodium excretion was reduced by ∼50% (to 70 ± 30 mmol/day), and conduit (brachial artery flow-mediated dilation [FMDBA]) and resistance (forearm blood flow responses to acetylcholine [FBFACh]) artery EDD were 68% and 42% (peak FBFACh) higher following DSR (p < 0.005). Low sodium markedly enhanced NO-mediated EDD (greater ΔFBFACh with endothelial NO synthase inhibition) without changing endothelial NO synthase expression/activation (Ser 1177 phosphorylation), restored BH4 bioactivity (less ΔFMDBA with acute BH4), abolished tonic superoxide suppression of EDD (less ΔFMDBA and ΔFBFACh with ascorbic acid infusion), and increased circulating superoxide dismutase activity (all p < 0.05). These effects were independent of ΔSBP. Other subject characteristics/dietary factors and endothelium-independent dilation were unchanged. DSR largely reversed both macro- and microvascular endothelial dysfunction by enhancing NO and BH4 bioavailability and reducing oxidative stress. Our findings support the emerging concept that DSR induces “vascular protection” beyond that attributable to its BP-lowering effects.